Muisteltu ja kirjoitettu evakkomatka : Tutkimus evakkolapsuuden muistelukerronnan poetiikasta - Savolainen, Ulla (2017)
As a result of the Winter War (1939 1940) and the Continuation War (1941 1944), Finland ceded territories of Karelia to the Soviet Union. There was a Finnish population of over 400,000 people living in the ceded area at that time, and this population was evacuated to the Finnish side of the new border. The evacuation generated narratives about the evacuation journey. Later on, the evacuation journey has itself become a symbol enriched with meanings, a symbol that seems to characterize memories and reminiscences of Karelian evacuees more than any other theme. The research of the present thesis explores the poetics and rhetorical techniques of reminiscence writings about childhood evacuation journeys. The methodological foundation of the research combines theories of folkloristics, oral history research and narrative research. Memories and reminiscences are a fascinating area to explore because they are, according to the approach used here, the contemporary, personal and also narrative interpretations given to the past as well as rendering the significance the individuals assigned to it. Accordingly, the topic of this research is not so much childhood as it was in the past but childhood as it is formulated in writings at the moment of reminiscing. In the case of former Karelian child evacuees, both childhood and the childhood home are remote in time and in space. Narrative reminiscing operates as a tool for handling and crossing this distance. It is a means of creating and analyzing the relationship between the past, the present and the future. The research reveals three narrative strategies: 1. Truth and history oriented narrative strategy 2. Reflexive narrative strategy 3. Literary narrative strategy These strategies are illustrated through three different ways of how writers describe the evacuation journey. Strategies are also characterized by certain kinds of intertextual connections on the one hand and the writer s different ways of handling time in narration on the other. These narrative strategies are ...